Utilization of Remittance at Household Level: A Case of Khanigaun Village of Resunga Municipality, Gulmi District - Khatri, Bishnu B. (Nepalese Journal of Development and Rural Studies, 2017)
The rural out-migration for labour of Nepal is a common livelihood strategy at household level. The paper tries to assess the utilization of rural-out migrants’ remittance at household level in Khanigaun Village of Resunga Municipality, Gulmi District. The study is mainly based on primary data and utilized mixed method. The primary information collected through household survey and focus group discussions techniques. 120 sample households were selected by using purposive sampling method. The targeted households were those where at least one family member of household who are working in the foreign country or who worked foreign country and have returned now as a labour migration. The data revealed that the major bulk of remittances were used for consumption purposes. Though, household investment in business or traditional productive sectors and savings were rather small, but remittances were also seen as important financial means for investment in human capital (i.e. education, health and hygiene), housing and land purchase. The importance of the repayment of the cost of migration should not be underestimated. Finally, the study concludes that most of migrant families had improved their living standard to some extent from the remittance money so far, either they used productive or not is in the debate. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page: 12-20